Management of achilles tendon injury: A current concepts systematic review. - Gulati,V; Jaggard,M; Al-Nammari,SS; Uzoigwe,C; Gulati,P; Ismail,N; Gibbons,C; Gupte,C (World J Orthop, 2015)
Achilles tendon rupture has been on the rise over recent years due to a variety of reasons. It is a debilitating injury with a protracted and sometimes incomplete recovery. Management strategy is a controversial topic and evidence supporting a definite approach is limited. Opinion is divided between surgical repair and conservative immobilisation in conjunction with functional orthoses. A systematic search of the literature was performed. Pubmed, Medline and EmBase databases were searched for Achilles tendon and a variety of synonymous terms. A recent wealth of reporting suggests that conservative regimens with early weight bearing or mobilisation have equivalent or improved rates of re-rupture to operative regimes. The application of dynamic ultrasound assessment of tendon gap may prove crucial in minimising re-rupture and improving outcomes. Studies employing functional assessments have found equivalent function between operative and conservative treatments. However, no specific tests in peak power, push off strength or athletic performance have been reported and whether an advantage in operative treatment exists remains undetermined.